2020
DOI: 10.3390/genes11030320
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis and Function Prediction of Long Noncoding RNAs in Sheep Pituitary Gland Associated with Sexual Maturation

Abstract: Long noncoding RNA (lncRNA) plays a crucial role in the hypothalamic-pituitary-testis (HPT) axis associated with sheep reproduction. The pituitary plays a connecting role in the HPT axis. However, little is known of their expression pattern and potential roles in the pituitary gland. To explore the potential lncRNAs that regulate the male sheep pituitary development and sexual maturation, we constructed immature and mature sheep pituitary cDNA libraries (three-month-old, TM, and nine-month-old, NM, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 68 publications
0
22
0
1
Order By: Relevance
“…Several comparable studies in sheep pituitaries were performed to explore the functions of lncRNAs in sexual maturation and reproductive function. Comparison of the lncRNAs in pituitaries of immature and mature rams revealed 2417 known lncRNAs and 1256 new lncRNAs, including 193 that were DE ( 134 ), while 1407 DE mRNAs were identified. For the DE protein-coding genes related to growth, reproduction, or steroid synthesis, interactions with the lncRNAs were predicted and networks constructed.…”
Section: Screening For Functional Pituitary Lncrnas Associated With Sexual Maturation and Reproductive Functionmentioning
confidence: 99%
“…Several comparable studies in sheep pituitaries were performed to explore the functions of lncRNAs in sexual maturation and reproductive function. Comparison of the lncRNAs in pituitaries of immature and mature rams revealed 2417 known lncRNAs and 1256 new lncRNAs, including 193 that were DE ( 134 ), while 1407 DE mRNAs were identified. For the DE protein-coding genes related to growth, reproduction, or steroid synthesis, interactions with the lncRNAs were predicted and networks constructed.…”
Section: Screening For Functional Pituitary Lncrnas Associated With Sexual Maturation and Reproductive Functionmentioning
confidence: 99%
“…Then, Feng et al (2018) identified 5 lncRNAs and 76 mRNAs in ovaries of Hu sheep with high and low prolificacy, respectively [ 15 ]. Yang et al (2020) analyzed lncRNA and mRNA in male sheep pituitary and found that 5 candidate lncRNAs and their targeted genes enriched in growth and reproduction related pathways [ 16 ]. Su et al (2020) screened differential lncRNA through high-throughput sequencing, concluded that XLOC-2222497 and its target AKR1C1 could interact with progesterone in porcine endometrium for controlling pregnancy maintenance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the animal quantitative trait loci database suggested 1 intronic and 6 intergenic lncRNAs as candidates of sheep fat-tail development. Transcriptome analyses were performed in speci c sheep tissues to reveal the potential regulatory roles of lncRNAs, such as in the skeletal muscle [11,12,13], pituitary [14,15,16], testis [17,18], and ovaries [19,20,21]. However, related research on lncRNA in sheep tail fat is still lacking, including the regulation mechanism of fat deposition and related molecular pathways of tail fat development.…”
Section: Introductionmentioning
confidence: 99%